2020
DOI: 10.3390/ijgi9110689
|View full text |Cite
|
Sign up to set email alerts
|

Panoramic Mapping with Information Technologies for Supporting Engineering Education: A Preliminary Exploration

Abstract: The present researchers took multistation-based panoramic images and imported the processed images into a virtual tour platform to create webpages and a virtual reality environment. The integrated multimedia platform aims to assist students in a surveying practice course. A questionnaire survey was conducted to evaluate the platform’s usefulness to students, and its design was modified according to respondents’ feedback. Panoramic photos were taken using a full-frame digital single-lens reflex camera with an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Some of these virtual images uses official data (e.g., topographic databases Halik [17]) and are used by leisure industries to attract tourists [18]. Lai et al [19] performed a research about processing panoramic images for a VR environment integrated in a multimedia platform. This study contributed especially to improving panoramic photography and image stitching quality, proposed a strategy for producing high quality panoramic images, combination of information technologies, and assessing teaching effectiveness through the multimedia platform.…”
Section: New Visualization Methodsmentioning
confidence: 99%
“…Some of these virtual images uses official data (e.g., topographic databases Halik [17]) and are used by leisure industries to attract tourists [18]. Lai et al [19] performed a research about processing panoramic images for a VR environment integrated in a multimedia platform. This study contributed especially to improving panoramic photography and image stitching quality, proposed a strategy for producing high quality panoramic images, combination of information technologies, and assessing teaching effectiveness through the multimedia platform.…”
Section: New Visualization Methodsmentioning
confidence: 99%
“…The name "panorama" was invented by the English painter Robert Barker in 1787 for his paintings shown on a circular surface. The term panorama is derived from the Greek words pan ('all') and horama ('view') [19]. M. Garrela of England, patented a camera that rotated around its own axis in 1857, and it accomplished the job.…”
Section: Panoramamentioning
confidence: 99%
“…Image stitching is performed on two images. To detect the stitching position, pattern matching calculates the offset amount between the reference image and the comparison image in each region for each of the two images [19]. The two images are then transformed into a spherical image format using the determined stitching position and the features of each optical lens system.…”
Section: Fig 12 Image Processingmentioning
confidence: 99%
“…Michitaka [14] discussed how virtual panoramas could be used to increase public interest in exhibitions and theaters. Lai et al [15] employed VR and panoramic photography to establish a website for students to take a surveying practice course and reported that 92% of the study participants considered the website helpful to the course learning process. Studies on VR applications in engineering education, mechanical design, and physical education training [16][17][18] have verified the utility of VR in education.…”
Section: Information-technology-based Visualizationsmentioning
confidence: 99%
“…In accordance with the approach proposed by [29], the 360° panoramas with a horizontal angle of 360° and a vertical angle of less than 180° were captured in this study. Panoramas are typically taken with one of two methods [15], namely by using a 360° spherical camera to directly produce panoramas or by placing one or more cameras on a platform to capture images and stitching the images together. Compared with the second strategy, the first is simpler and more convenient but usually has a lower resolution and limited capability of customized functionality.…”
Section: Information-technology-based Visualizationsmentioning
confidence: 99%